The musical madhouse = Les grotesques de la musique - Berlioz, Hector, 1803-1869 (Eastman studies in music., 2003)
"The Musical Madhouse is the first complete translation into English of Hector Berlioz's Les Grotesques de la musique. It is the funniest of all his works, and consists of a number of short anecdotes, witticisms, open letters, and comments on the absurdities of concert life. Alastair Bruce's translation brings to life this important composer and bon vivant. He does a wonderful job of conveying all the puns, jokes, and invective of Berlioz's prose as well as the nuances of his stories. He even imitates a Tahitian accent in the translation, as Berlioz does in the original. The notes will give the reader insight into the innuendos and in-jokes that fill the pages. This translation will take its place among other translations of Berlioz's prose writings, bringing to the reader more lively examples of a still misunderstood composer caught up in the musical life of mid-nineteenth century Paris."--Jacket